Technical and Economical Evaluation of Power Saving Consumer Electrical Engineering Efficiency Under market Condituions - Y. N. Kolesnik; A. V. Ibaneychik (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper considers an evaluation and justification of power saving efficiency and potential due to installation of power saving electric devices in the housing sector with due account of functioning of market conditions. A number of nomographs have been developed on the basis of modern methods for efficiency evaluation and technical and economical model that make it possible to evaluate efficiency of power-saving equipment. On the one side these nomographs take into account power consumption, service life and mode of electric device operation and on the other side they also take account of equipment and electric power price and bank rate. Evaluation of economically justified potential of power saving has been carried out on the basis of these models.